2021
DOI: 10.1111/jocs.15433
|View full text |Cite
|
Sign up to set email alerts
|

Robotically assisted coronary artery bypass graft surgery versus drug‐eluting stents for patients with stable isolated proximal left anterior descending disease

Abstract: Objective To compare the midterm outcomes of patients with isolated left anterior descending disease (iLAD) who underwent robotically assisted coronary artery bypass graft (R‐CABG) and percutaneous coronary intervention (PCI) with drug eluting stents (DES). Method Clinic data was collected in 223 patients who underwent R‐CABG in our hospital between July, 2007 to November, 2014. Cardiology Database System of our hospital was used to identify 4047 patients who underwent PCI with DES for LAD lesion between April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Minimally invasive CABG is associated with a ten-year survival of 76-90% (40,41,43,44,47) and freedom from MACCE of 70-85% (40,43,44). The incidence of target vessel reintervention following minimally invasive CABG is ≤5% (37,(42)(43)(44)47,49,50), which is significantly lower than PCI for isolated LAD disease (37,42,45,49,50).…”
Section: Clinical Resultsmentioning
confidence: 98%
“…Minimally invasive CABG is associated with a ten-year survival of 76-90% (40,41,43,44,47) and freedom from MACCE of 70-85% (40,43,44). The incidence of target vessel reintervention following minimally invasive CABG is ≤5% (37,(42)(43)(44)47,49,50), which is significantly lower than PCI for isolated LAD disease (37,42,45,49,50).…”
Section: Clinical Resultsmentioning
confidence: 98%
“…17,[42][43][44] While Lee, Moreyra, and Yin investigated outcomes following OPCAB and PCI. [45][46][47] A total of 251,740 patients were included in all studies, although the vast majority of patients (246,832) were enrolled in 1 study. 46 Data collection dates ranged from 2001 to 2017.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…However, the optimal revascularization strategy for isolated LAD lesions remains controversial. Several recent randomized controlled trials (RCTs), observational studies, and meta-analyses revealed no additional benefit in survival and MACEs from MIDCAB compared with PCI [Blazek 2013;Blazek 2015;Li 2021]. Nevertheless, other reports have demonstrated that MIDCAB offered superior freedom from MACEs in comparison with PCI [Etienne 2013;Iakovou 2002].…”
Section: Introductionmentioning
confidence: 99%